Integrating Biochar and Fungal Inputs in Sandy Soil Systems for Chili Production - Maryam; Rahim, Iradhatullah; Suherman (Integrated and Sustainable Agriculture, 2025)
Sandy soils are widely recognized as marginal agricultural lands due to low water retention, weak nutrient-holding capacity, and limited biological activity. This study aimed to evaluate the effects of integrating biochar and Pleurotus sp. on soil functionality and chili (Capsicum annuum L.) productivity in sandy soil systems. The experiment was conducted using a completely randomized design with four treatments: control (no amendment), biochar alone, Pleurotus sp. alone, and a combined biochar + Pleurotus sp. treatment. Plant growth parameters, leaf chlorophyll content, yield components, and total fruit yield were measured. The results showed that the combined biochar and Pleurotus sp. treatment consistently produced the highest plant height, chlorophyll content, fruit number, and total yield compared with single-input and control treatments. These improvements were attributed to synergistic interactions between biochar-induced improvements in soil physical properties and Pleurotus sp.-driven biological processes, including organic matter decomposition and nutrient mineralization. This study provides empirical evidence that integrating biochar and fungal inputs enhances nutrient cycling efficiency and root–soil–microbe interactions in sandy soils. The findings highlight the potential of biochar–fungal integration as a sustainable and scalable strategy for improving productivity on marginal lands and supporting climate-resilient agricultural systems.